This is a differential equations problem. We are to work backwards and determine the function f(x) when given f "(x) and initial values.
<span>f ''(x) = 12x^2 + 6x − 4, when integrated with respect to x, yields:
x^3 x^2
f '(x) = 12------ + 6----- - 4x + C, or 4x^3 + 3x^2 - 4x + C, and
3 2
x^4 x^3 x^2
f(x) = 4------- + 3------- - 4------ + Cx + D, or f(x)=x^4 + x^3 - 2x^2 + Cx + D
4 3 2
Now, because f(0)=5, 5=0^4 + 0^3 -2(0)^2 + C(0) + D, so that D=5.
Determine D in the same manner: Let x=1 and find the value of C.
Then the solution, f(x), is x^4 + x^3 - 2x^2 + Cx + 5. Replace C with this value and then you'll have the desired function f(x).</span>
Answer:
I have never heard of it sorry
Answer:
C
Step-by-step explanation:
Given 2 secants intersect a circle from a point outside the circle, then
The product of the external part and the entire part of one secant is equal to the product of the external part and the entire part of the other secant, that is
x(x + 10 + x) = 6(6 + 10 + x)
x(2x + 10) = 6(16 + x) ← distribute parenthesis on both sides
2x² + 10x = 96 + 6x ← subtract 96 + 6x from both sides
2x² + 4x - 96 = 0 ← in standard form
Divide through by 2
x² + 2x - 48 = 0 ← factor the left side
(x + 8)(x - 6) = 0
Equate each factor to zero and solve for x
x + 8 = 0 ⇒ x = - 8
x - 6 = 0 ⇒ x = 6
However x > 0 ⇒ x = 6 → C
Hello.
There is only one solutin for <span> x^2 + 10x + 25 = 0
You can tell because it ends with a 0.
Have a nice day</span>
Answer:
n = 13
Step-by-step explanation:
20= -6+2n
Add 6 to each side
20+6= -6+6+2n
26 = 2n
Divide each side by 2
26/2 = 2n/2
13 =n